THE MASTERY OF TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) ON PRE-SERVICE ENGLISH TEACHERS - Nurhayati Sitorus; Rina Oktavia Simarmata; Sahlan Tampubolon; Eva Dita Yanti Simanjuntak (Jurnal Basataka (JBT), 2024)
The research has objective to analyze the ability of pre-service English teachers in TPACK. TPACK is a framework that explains the integration of technology in teaching by emphasizing the interaction between three main knowledges, namely Technological Knowledge (TK), Pedagogical Knowledge (PK), and Content Knowledge (CK). This study uses qualitative research. The respondents in this study were pre-service English teacher students at FKIP Universitas HKBP Nommensen. Data were obtained through questionnaires that given to respondents by using Likert scales. Then, data was analyzed by using Miles and Huberman taht consist of three stages, namely, data reduction, displaying data, and drawing conclusion (verification) . The results of the study showed that the ability of prospective teachers in TPACK was categorized as good with an average 75,1.